DECLARATIVE SPEECH ACT FOUND IN STEVEN SPIELBERGâ€™S â€œREADY PLAYER ONEâ€ - Tri Murtini, Dewi; Ambalegin, Ambalegin (Linguistik : Jurnal Bahasa dan Sastra, 2022)
This research used descriptive qualitative method to find out the types of declarative speech acts found in Steven Spielbergâ€™s â€œReady Player Oneâ€. The data were collected using observational non-participatory method. The data used were taken from the utterances and narratives that contained declarative speech acts by the characters in the movie. The data were analyzed using the theory of declarative speech acts proposed by Searle Vanderveken (1985). The data were also equalized using pragmatic identify method. In addition, the technique in this research involved pragmatic competence used in equalizing the theory of Sudaryanto (2015). The result of the research showed that there were 15 utterances that contained declarative speech acts found in Steven Spielberg â€œReady Player Oneâ€. There were 5 data showed declaring, 1 data showed appointing, 1 data showed denouncing, 3 data showed approving and 5 data showed disapproving. Disapproving and declaring were the most common declarative speech acts found in the movie because the characters had a lot of disagreement in the movie.